ANALISIS PENGAMBILAN KEPUTUSAN ATAS IDLE CAPACITY (STUDI PADA PT. XYZ) DI MAKASSAR - Mince Batara (Paulus Journal of Accounting (PJA), 2020)
This research aims to analysis the idle capacity experienced by PT. XYZ and calculating the break event point as a basic of minimum production that must be achieved in order to reach maximum profit and calculate the basic of rental rate which can get the profit. In this research used qualitative method and the case study method, qualitative method were chosen to get the widest possible informationThe results of the research indicate that in 2018 PT. XYZ reaches the break event point of Rp.19,573,616,842.25 the cost of goods sold is Rp.22,138,154,627.74, so that the company can be minimized cost because the result was bigger more than BEP.Idle capacity was leased in two alternatives, were: (1) rent out machines which unemployed when raw materials were available, (2) rent out machines and direct labor. From this research, it was found that the freezing engine rental rates that apply in 2018 Rp. 1,500 / kg was smaller than the standard rent expenses that should have been used Rp. 1,680 / kg, but management did not have room to increase rent expenses because the rent expenses apply to more competing companies smaller than the rented expenses at PT. XYZ. But if the idle capacity used capacity of the machine and labor simultaneously, it can contribute profit to the company where the rent expenses apply Rp. 7,500 while the standard rent expenses is Rp. 6,675.